Nurse triage in theory and in practice. Issue 3 (September 1993) - George, S; Read, S; Westlake, L; Williams, B; Pritty, P; Fraser-Moodie, A
Abstract : 'Nurse Triage' refers to the formal process of early assessment of patients attending an accident and emergency (A&E) department by a trained nurse, to ensure that they receive appropriate attention, in a suitable location, with the requisite degree of urgency. The benefits claimed for nurse triage include better patient outcomes, through clinical management reaching those in greatest need of it first. A recent study of nurse triage in a British A&E department failed to demonstrate the benefits claimed: patients undergoing triage were delayed, especially those in the most urgent groups. No differences were noted between the two study groups in levels of satisfaction with the A&E process. The results brought forth criticism from all quarters. In this paper the points made by the critics are considered, and an attempt to answer them is made.